2015
DOI: 10.3835/plantgenome2015.01.0001
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Characterization of Interspecific Hybrids and an Admixture Population Derived from Panicum amarum × P. virgatum

Abstract: Switchgrass (Panicum virgatum L.) and its relatives are regarded as top bioenergy crop candidates; however, one critical barrier is the introduction of useful genetic diversity and the development of new cultivars and hybrids. Combining genomes from related cultivars and species provides an opportunity to introduce new traits. In switchgrass, a breeding advantage would be achieved by combining the genomes of intervarietal ecotypes or interspecific hybrids. The recovery of wide crosses, however, is often tediou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…We show that the transgenes are stably inherited and expressed using selectablable markers or reporter genes. In a previous paper (Heffelfinger et al, 2015), we showed that transgenes can be segregated to yield non-GMO hybrids in F 1 BC 1 populations. We have also used genomic analysis to confirm the identity of the parents for each F 1 offspring using the ratio of sites where neither of the two offspring alleles (transgressive events) were present in the parent compared to the total number of sites.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…We show that the transgenes are stably inherited and expressed using selectablable markers or reporter genes. In a previous paper (Heffelfinger et al, 2015), we showed that transgenes can be segregated to yield non-GMO hybrids in F 1 BC 1 populations. We have also used genomic analysis to confirm the identity of the parents for each F 1 offspring using the ratio of sites where neither of the two offspring alleles (transgressive events) were present in the parent compared to the total number of sites.…”
Section: Discussionmentioning
confidence: 97%
“…Genomic DNA was prepared as described in Heffelfinger et al . (). Twenty‐seven samples (eight parents and nineteen offspring) were sequenced via genotyping‐by‐sequencing (Heffelfinger et al ., ) on one Illumina Hi‐Seq 2500 lane at the Yale Center for genome analysis.…”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations